2022
DOI: 10.1002/jor.25436
|View full text |Cite
|
Sign up to set email alerts
|

Cervical disc arthroplasty combined with two‐level ACDF for the treatment of contiguous three‐level cervical degenerative disc disease: A comparative study

Abstract: To compare the differences among constructs with one‐level cervical disc arthroplasty (CDA) and two‐level anterior cervical discectomy and fusion (ACDF). A retrospective study was conducted involving patients who underwent one‐level CDA and two‐level ACDF between June 2012 and July 2020. According to the different locations of CDA and ACDF, we divided the constructs into three types: type Ⅰa: CDA‐ACDF‐ACDF; type Ⅰb: ACDF‐CDA‐ACDF; type Ⅰc: ACDF‐ACDF‐CDA. The differences of clinical and radiological outcomes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Previous studies reported that the rate of cage nonfusion after ACDF was less than 10% at 1‐year follow‐up 32 . However, in the early period after ACDF (during the first 90 days postoperatively), the fusion rate was much lower (15%–62%) at 3‐month follow‐up 33–36 . Lower fusion rates in the early period would result in higher rates of subsidence, cage displacement, and pseudarthrosis.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Previous studies reported that the rate of cage nonfusion after ACDF was less than 10% at 1‐year follow‐up 32 . However, in the early period after ACDF (during the first 90 days postoperatively), the fusion rate was much lower (15%–62%) at 3‐month follow‐up 33–36 . Lower fusion rates in the early period would result in higher rates of subsidence, cage displacement, and pseudarthrosis.…”
Section: Discussionmentioning
confidence: 98%
“…Following radiographic recommendations for evaluating cervical fusion, 39,40 fusion was defined as the presence of continuous bone bridges behind the surgical segments on CT three‐dimensional reconstruction. According to our previous study, ‘fusion’ is defined as the presence of ≤2°or 3°motion and/or ≤2 mm of motion of the interspinous distance on flexion–extension X‐rays 33–36,41 . Further, different implant and surgical procedures, as well as screw length and angle, would result in a different fusion rate 9 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Huang et al 46 investigated the outcomes among 3 subtypes of Type 1 HS constructs (Type Ia: CDA-ACDF-ACDF; Type Ib: ACDF-CDA-ACDF; Type Ic: ACDF-ACDF-CDA. All groups showed significant improvement in PROs by 1-year follow-up.…”
Section: Three-level Constructsmentioning
confidence: 99%